THE COLECCIÓN PALEONTOLOGÍA DE VERTEBRADOS LILLO, A PIONEERING ROLE IN THE RESEARCH ON FOSSIL VERTEBRATESIN ARGENTINA - Pablo E. Ortiz; Rodrigo González; Virginia Deraco; Claudia Herrera; Fernando Abdala; Graciela Esteban; Agustín Martinelli (Publicación Electrónica de la Asociación Paleontológica Argentina, 2025)
Fossils collected by Abel Peirano from Catamarca and Tucumán in the late 1930s constituted the basis for the creation of the Colección Paleontología de Vertebrados Lillo (PVL) in Tucumán. The collection was formally founded in 1957 as Laboratorio de Vertebrados Fósiles (LVF) by Osvaldo Reig, who led many field trips that resulted in the publication and incorporation of emblematic materials from the South American Mesozoic. José Bonaparte became the director of the LVF in 1960, incorporating a large number of Mesozoic fossils from northwest Argentina, Cuyo, and Patagonia. These findings represented an enormous qualitative and quantitative leap in the knowledge of Mesozoic faunas from Gondwana. In 1979, when the LVF was dissolved and the fossil collection became known as PVL, Jaime Powell succeeded Bonaparte as curator and began leading field trips to the Cretaceous and Cenozoic of northwest Argentina and Cretaceous of northern Patagonia, incorporating important material in the collection. In the 1980s, young researchers began to work on fossils stored at the PVL, studying Neogene birds and mammals and Mesozoic archosauriforms and cynodonts. In the 1990s, other scholars under Powell’s guidance focused their research on Cenozoic mammals, providing new and relevant material for the collection. Today the PVL has about 7,900 catalogued specimens (130 holotypes) and it represents one of the most important collections of vertebrate palaeontology in Argentina. In 2010, the collection was registered under the national authority on paleontological matters (Law 25.743) and became part of the Facultad de Ciencias Naturales-Instituto Miguel Lillo, Universidad Nacional de Tucumán.